2020
DOI: 10.1007/s12520-020-01254-4
|View full text |Cite
|
Sign up to set email alerts
|

Magdalenian and Epimagdalenian chronology and palaeoenvironments at Kůlna Cave, Moravia, Czech Republic

Abstract: Kůlna Cave is the only site in Moravia, Czech Republic, from which large assemblages of both Magdalenian and Epimagdalenian archaeological materials have been excavated from relatively secure stratified deposits. The site therefore offers the unrivalled opportunity to explore the relationship between these two archaeological phases. In this study, we undertake radiocarbon, stable isotope (carbon, nitrogen and sulphur), and ZooMS analysis of the archaeological faunal assemblage to explore the chronological and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 86 publications
0
10
0
Order By: Relevance
“…It has also been demonstrated that a decrease in human population of the CB took place at the end of the Late Epigravettian 8 . So far only Lovas (14–13 ka cal BP) 72 , and a stray find from Mezőlak (13.7–13.46 ka cal BP) 73 , 74 are known from Transdanubia that are contemporaneous with the Epi-Magdalenian Culture of Czechia 75 and the Arched Backed Point techno complex of Poland 76 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that a decrease in human population of the CB took place at the end of the Late Epigravettian 8 . So far only Lovas (14–13 ka cal BP) 72 , and a stray find from Mezőlak (13.7–13.46 ka cal BP) 73 , 74 are known from Transdanubia that are contemporaneous with the Epi-Magdalenian Culture of Czechia 75 and the Arched Backed Point techno complex of Poland 76 .…”
Section: Discussionmentioning
confidence: 99%
“…Geographic origin of raven: as a tracking isotope, sulfur can provide important information on the origin, movement and migratory behavior of animals [143][144][145][146] . Similar to δ 13 C and δ 15 N, δ 34 S abundances in bone collagen change slowly and depend on individual and bone-speci c turnover rates.…”
Section: Data Availabilitymentioning
confidence: 99%
“…A local Pavlovian δ 34 S baseline was set by using the area between the 25% and 75% quantiles of δ 34 S abundances of all published herbivores from Předmostí I 76 , resulting in a local δ 34 S-reference spanning from +0.3 to +3.6 ‰. This approach to determine the local δ 34 S signal for further comparison is well-established and has successfully been employed in previous archaeological and palaeoecological studies [143][144][145][146] . δ 34 S of Pavlovian ravens were plotted against the local δ 34 S baseline and three groups of ravens were isolated: local, non-local (low δ 34 S), and non-local (high δ 34 S).…”
Section: Data Availabilitymentioning
confidence: 99%
“…This variation has been interpreted as representing changes to baseline δ 15 N in response to climatic and environmental drivers. Most notably, a large decrease and then rapid increase in herbivore δ 15 N occurred during the Late Glacial, between approximately 17,000- and 12,000-years before present (BP) [ 15 17 , 20 23 , 25 , 26 ]. This trend occurs in multiple species, across a wide range of mid and high latitude environments and in recent years has been termed the Late Glacial Nitrogen Excursion (LGNE) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%